Morphological Assessment of the Protective Effects of A. muricata Seed Extract Against Potassium Dichromate Stomach Poisoning in Wistar Rats (FULafia Journal of Science and Technology, 2025)
This study investigated the protective effects of Annona muricata seed extract against potassium dichromate (K2Cr2O7) stomach poisoning in Wister rats. Seeds were extracted with ethanol, and 20 rats were divided into five groups. Group I received distilled water, Group II received 200 mg/kg extract, Group III received 20 mg/kg K2Cr2O7, Group IV received 20 mg/kg pbw of K2Cr2O7 followed by 200 mg/kg pbw of extract, and Group V received 200 mg/kg pbw of extract followed by 20 mg/kg pbw of K2Cr2O7. Group I showed normal liver and stomach morphology. Group II showed normal stomach morphology. Group III showed stomach damage, disruption of surface epithelium, and leukocyte infiltration. Group IV showed normal stomach morphology, while Group V showed no pathological lesions. Annona muricata seed extract protects against K2Cr2O7 stomach poisoning in Wistar rats, suggesting its potential against stomach poisoning in humans. Further molecular investigation is needed to understand the mechanism of action
Keywords: Annona muricata seeds; morphology; stomach; Wistar rats; Potassium dichromate; Poisoning